Upaya Peningkatan Ekonomi Jemaat melalui Pelatihan Produksi Virgin Coconut Oil (VCO) di GMIT Elim Sialain, Semau, Kabupaten Kupang - Jeane M Hendrik; Maya F Roman; Eka Citra Gayatri Kerihi; Abdonia W Finmeta; Deglory Tunmuni; Nardi M Leo; Anika Nabunome; Nur Aini Bunyani (Universitas Mataram, 2026)
Virgin Coconut Oil (VCO) is extracted coconut oil containing medium-chain fatty acids that are believed to have many health benefits. These fatty acids are easily digested and absorbed by the intestines because their molecules are relatively small, allowing the body to directly burn them to produce energy. Furthermore, VCO contains lauric acid, which can dissolve lipid membranes in the form of viruses, thus disrupting the immune system and inactivating the virus. VCO is processed without heating, without the addition of chemicals, dyes, or preservatives, allowing it to remain as pure vegetable oil without changing the composition or characteristics of the oil. VCO has high economic value. The manufacturing process is easy. The methods used in this Community Service are Counseling, hands-on practice, and discussion. It is hoped that the use of coconuts will not only be sold as unprocessed fruit, but that coconuts will be processed into pure coconut oil or Virgin Coconut Oil and can be developed more widely through group entrepreneurship programs, thereby increasing the income of the congregation, especially in the GMIT Elim Sialain Congregation, Uitao Village, Semau District, Kupang Regency.